2006
DOI: 10.1177/107602960601200208
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Complications in Patients Treated with Anticoagulant Doses of a Low Molecular Weight Heparin (Enoxaparin) in Routine Hospital Practice

Abstract: Low molecular weight heparins (LMWHs) are a rapidly growing class of anticoagulant drug. Their efficacy has been demonstrated in several clinical settings where they are rapidly becoming the anticoagulant of choice. Controlled clinical studies in patients with deep vein thrombosis, pulmonary embolism, and unstable angina have documented that the frequency of major hemorrhage is 0.5-4%. The purpose of the study was to determine the frequency of minor and major hemorrhage occurring in patients receiving anticoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…Moreover, because anticoagulation carries a risk of fatal bleeding complications [13,22], all-cause mortality appears a more appropriate marker for comparison because mortality incorporates all cost-benefit effects of prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because anticoagulation carries a risk of fatal bleeding complications [13,22], all-cause mortality appears a more appropriate marker for comparison because mortality incorporates all cost-benefit effects of prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the fact that patients who experienced bleeding events with low doses appeared to have at least one risk factor for bleeding: age [75 years (50%), an abnormal prothrombin time (12.5%), a baseline platelet count \100 9 10 3 /mm 3 (25%), CrCl \30 ml/min (37.5%), anemia (37.5%) and co-administration of other anticoagulants such as aspirin and clopidogrel (50%). Similar risk factors for bleeding in patients receiving enoxaparin were identified in two observational studies [30,38,39]. Since higher anti-Xa levels correlate with increased risk of major bleeding in dose-investigating studies [40], monitoring of anti-Xa levels can improve the safety of enoxaparin especially in patients at risk of bleeding [41].…”
Section: Discussionmentioning
confidence: 83%
“…Spicer et al [36] demonstrated that weight estimation results in inaccurate dosing in 51% of cases because of the tendency to overestimate the weight of lighter patients and underestimate it in heavier patients [37]. The most important side effect of anticoagulant therapy is bleeding [38] which occurred in 23 patients (5%) with the highest rate observed in the VTE prophylaxis group and patients taking the lower inappropriate doses. This can be explained by the fact that patients who experienced bleeding events with low doses appeared to have at least one risk factor for bleeding: age [75 years (50%), an abnormal prothrombin time (12.5%), a baseline platelet count \100 9 10 3 /mm 3 (25%), CrCl \30 ml/min (37.5%), anemia (37.5%) and co-administration of other anticoagulants such as aspirin and clopidogrel (50%).…”
Section: Discussionmentioning
confidence: 95%
“…LMWHs might also be overdosed, however, resulting in severe bleeding complications [21][22][23][24][25][26][27][28]. The plasmatic LMWH action should therefore be monitored especially for renal-insufficient patients [29,30], pregnant patients [31][32][33], patients with abnormal body weight [34], children [35], or patients with high risk of bleeding or thrombosis [1].…”
Section: Discussionmentioning
confidence: 99%